Population‐based study of presbyopia in Nicaragua. (10th July 2016) - Hookway, Larry A; Frazier, Marcela; Rivera, Nelson; Ramson, Prasidh; Carballo, Luis; Naidoo, Kovin
Abstract : Background: Uncorrected presbyopia can greatly impact a person's quality of life and employment prospects. Nicaragua is the poorest country in Latin America and there are no population‐based reports of prevalence of presbyopia in Nicaragua. Methods: A cross‐sectional population‐based household survey was conducted. The sample was selected through random cluster sampling. Adults 35 years and older were enlisted through a door‐to‐door method using aged‐based sampling. All enumerated household members 35 years and older were asked to attend a free visual acuity screening. Autorefraction was done and then uncorrected distance vision and near visual acuity were measured for all subjects. All those who had distance or near vision that was 6/12 or worse underwent a clinical examination, which included refraction at distance and near. Free spectacles were provided. Results: Of the 3, 390 subjects surveyed, 37.1 per cent reported that they wore spectacles on a regular basis. A total of 1, 871 (55.2 per cent) of those enumerated were examined. The prevalence of near visual impairment (6/12 [N 6] or worse) was 79.6 per cent for the 35 to 49‐year‐old group, 97.3 per cent for the 50 to 64‐year‐old group and 96.7 per cent for the 65 and over group. Of those reporting for the examination, 82.2 per cent did not have glasses. Of those examined, 10 per cent did not need spectacles, four per cent were given spectacles for distance only, 38 per cent spectacles for distance and near, 42 per cent spectacles for near only and seven per cent were referred for medical evaluation due to ocular pathology. During the refractions, 91.5 per cent were corrected to 6/12 or better at distance and 89.4 per cent were corrected to 6/12 or better at near. Conclusion: The majority of the participants who were examined did not have the spectacles that they needed. Over one‐third of those participants who presented without spectacles had distance vision better than 6/12 and could be improved to good near vision with ready‐made near‐only spectacles.